Change in weight-based bias over a decade: A longitudinal nationally representative survey - Elizabeth A Chivers; Kumar Yogeeswaran; Elena Zubielevitch; Chris G Sibley (Elsevier, 2022)
Summary: Background: Globally, the prevalence of obesity has almost tripled in the last 45 years, and almost 2 billion adults are considered overweight or obese. Such individuals have been shown to experience bias and stigma in their everyday life. While some prior research suggests that there has been an increase in weight-based bias over time, there have also been active efforts to counteract weight-based bias over the past decade. The current study uses cohort-sequential growth curve modelling on a nationally representative survey to examine change in weight-based bias over the last decade. The study also investigates whether changes in weight-based bias reflect developmental changes that occur with age, or whether there are cohort-based differences in such bias. The current study also examines whether there are gender differences in weight-based bias over the past decade. Methods: We used data from the New Zealand Attitudes and Values Survey (NZAVS). The NZAVS is an ongoing study that has been conducting an annual longitudinal panel survey of adult New Zealanders since 2009. There were 61,051 participants who responded to at least 1 out of the 11 waves available from the NZAVS. We used a feeling thermometer measure to assess attitudes toward people who are overweight over eleven years. Findings: We found that weight-based bias has remained relatively stable over the last decade. Small cohort-based differences occurred for women within four younger birth cohorts (those born 1990-1986; 1980-1976; 1975-1971; and 1970-1966) revealing a small increase in warmth towards people who are overweight. Both men and women showed a slight gradual increase in warmth toward people who are overweight, which peaked in middle age. Interpretation: Weight-based bias appears relatively stable over the past decade. These small changes do not appear to reflect developmental changes as a function of ageing. However, small decreases in weight-based bias among younger birth cohorts of women may reflect shifting societal norms about the acceptability of weight-based bias, although future work is needed to better understand this. Funding: Collection of the NZAVS data analysed in this paper was supported by a grant from the Templeton Religion Trust (TRT0196) awarded to the last author.